2014
DOI: 10.5688/ajpe7810181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Student Factors Associated with Pre-NAPLEX Scores

Abstract: Objective: To examine relationships among students' Pre-NAPLEX scores and prepharmacy, pharmacy school, and demographic variables to better understand factors that may contribute to Pre-NAPLEX performance. Methods: A retrospective review of pharmacy students' Pre-NAPLEX scores, demographics, prepharmacy factors, and pharmacy school factors was performed. Bivariate (eg, ANOVA) and correlational analyses and stepwise linear regression were conducted to examine the significance of various factors and their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
(19 reference statements)
0
15
1
Order By: Relevance
“…The literature is replete with studies investigating potential predictors of standardized test scores; Pharmacy Curriculum Outcomes Assessment (PCOA) test scores, 6,7 pre-North American Pharmacist Licensure Examination (NAPLEX) test scores, 8 and NAPLEX test scores. 9 For predicting OSCE performance, there has been limited work in pharmacy education 10 and health professions education.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…The literature is replete with studies investigating potential predictors of standardized test scores; Pharmacy Curriculum Outcomes Assessment (PCOA) test scores, 6,7 pre-North American Pharmacist Licensure Examination (NAPLEX) test scores, 8 and NAPLEX test scores. 9 For predicting OSCE performance, there has been limited work in pharmacy education 10 and health professions education.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…However, newer data, although limited by a single institution and pre-NAPLEX outcomes, are not strongly indicative of this relationship. 30 In terms of leadership and faculty qualifications, Popovich and colleagues 17 and Brazeau 31 suggest a link between leadership and program outcomes. Popovich and colleagues 17 further contest that many programs rely on faculty and administrators with minimal practice knowledge or academic experience to deliver core components of program curricula.…”
Section: Resultsmentioning
confidence: 99%
“…Relative risk ratios below 3 are viewed with suspicion. 8 For phase 1, selection of the best proxy for end-ofprogram (terminal) GPA performance, student scores for first semester GPA (GPA1), cumulative GPA at the end of the didactic curriculum (GPA6), cumulative GPA at the end of the curriculum (GPA8), NAPLEX first attempt score, and MPJE first attempt score were analyzed to determine the correlation between the variables. The bottom decile percentile rank scores for GPA6 and GPA8 were compared to on-time graduation, NAPLEX failure, and MPJE failure dummy variables using a cross tabulation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…7 Chisholm-Burns et al found significant correlations between pre-NAPLEX performance and Pharmacy College Admission Test (PCAT) scores, race/ethnicity, and pharmacy school GPA. 8 Alston and colleagues studied prepharmacy and first semester performance to identify variables that could be used to identify students most at risk to fail to graduate on time. Students with a first semester GPA below 3.0 were 17.6 times more likely to fail, and students with a second semester GPA below 3.0 were 35.8 times more likely to fail.…”
Section: Introductionmentioning
confidence: 99%